Efeito expansivo das transferências intergovernamentais e a interdependência espacial dos gastos públicos nos municípios brasileiros - Martins, Fernando Soares (2020)
This study aims to identify the presence of an expansive effect on lump-sum intergovernmental transfer from the Federal government or States to Brazilian municipalities (flypaper effect). Furthermore, we intend to analyze the existence of spatial dependence, and the occurrence of overflow of local public spending (spillover effect), i.e., how the expenditure of a municipality influence or are influenced by the expenditure of neighboring municipalities. For this purpose, cross-sectional data for the year 2010 from 4,563 Brazilian municipalities was used. The analysis was performed by means of the classical econometrics, using ordinary least squares and spatial econometrics techniques, where a spatial weights matrix was used based on the inverse of distance, associated with a spatial model with spatial lag in the dependent variable and in the residues. Our main results reveal the presence of the flypaper effect on the finances of Brazilian municipalities, and this effect is more intense in municipalities whose allied base of the elected mayor is proportionally greater than the opposition in the City Councils. On the other hand, the presence of politically strong neighboring municipalities leads to a reduction in municipal expenditures. The results indicate a spatial autocorrelation of municipal expenditures, pointing to a relationship of complementarity in expenditure decisions between neighboring municipalities.